The Utility of Serum IgG4 Concentrations as a Biomarker - Kawa, Shigeyuki (Hindawi Publishing Corporation, 2012)
IgG4-related disease is a new disease entity involving IgG4 in its clinical presentation and having 6 characteristic features: (1) systemic involvement; (2) solitary or multiple lesions showing diffuse or localized swelling, masses, nodules, and/or wall thickening on imaging; (3) high serum IgG4 concentration >135 mg/dL; (4) abundant infiltration of lymphoplasmacytes and IgG4-bearing plasma cells; (5) a positive response to corticosteroid therapy; and (6) complications of other IgG4-related diseases. To date, most IgG4-related diseases have been recognized as extrapancreatic lesions of autoimmune pancreatitis. This paper will discuss the utility of IgG4 as a biomarker of IgG4-related diseases, including in the diagnosis of autoimmune pancreatitis and its differentiation from pancreatic cancer, in the prediction of relapse, in the long-term follow-up of patients with autoimmune pancreatitis and normal or elevated IgG4 concentrations, and in patients with autoimmune pancreatitis and extrapancreatic lesions, as well as the role of IgG4 in the pathogenesis of IgG4-related disease.